Sustainable Agriculture Education through Processing Tobacco Stem into Liquid Organic Fertilizer - Karunia Irfan , Ramadahan; Ardhanesdian Rizqi , Setyadi; Haryuni, Haryuni; Achmad Fatchul, Aziez; Priyadi, Sapto; Mutiarra Ridyo Arum (Journal of Community Capacity Empowerment, 2025)
Processing agricultural waste into value-added products is an important step in supporting sustainable agriculture. One of the wastes that has great potential to be processed is tobacco stem waste, which is often considered as waste without value. This educational activity aims to provide knowledge and skills to farmers in processing tobacco stem waste into liquid organic fertilizer. This education is carried out through a participatory approach, involving counseling, technical demonstrations, and direct practice. The results of the activity showed that participants were able to understand the importance of waste management in supporting agricultural sustainability. Participants also succeeded in practicing the process of processing tobacco stem waste into liquid organic fertilizer, which includes shredding, fermentation using local microorganisms, and packaging the final product. The positive impacts of this activity include increasing farmer awareness of waste management, reducing dependence on chemical fertilizers, and cost efficiency in their farming systems. In addition, the application of liquid organic fertilizer from tobacco stems can also increase soil fertility naturally and support environmental conservation efforts. However, there are several challenges in implementing this activity, such as the lack of supporting facilities and the need for further assistance to ensure the sustainability of technology adoption by farmers. Overall, this educational activity has a positive impact on improving farmer skills and innovative waste management, while supporting more environmentally friendly and sustainable agriculture.